The role of philanthropy in enhancing education of B40 household: a proposed framework / Maimunah Johari, Hainnuraqma Rahim and Mohamed Saladin Abdul Rasool - Johari, Maimunah; Rahim, Hainnuraqma; Abdul Rasool, Mohamed Saladin (Center for Islamic Philantrophy & Social Finance (CIPSF), 2022)
Philanthropy plays an important role in alleviating the wellbeing of society. The role of philanthropy has been significant during the covid-19 pandemic, especially in the education sector which has led to the new norm of learning such as the open and distance learning (ODL) were implemented. Thus, technology becomes important, incurring additional costs for parents to acquire computers, handphones, and internet lines. As a result, various parties such as philanthropic organisations came forward to assist. However, the issue of transparency and accountability of these organisations also becomes the main highlight of the public. In addition, the effectiveness and efficiency of the assistance were also raised. Thus, this study aims to present a philanthropy framework in implementing new learning norms for B40 households, one of the worst groups affected by the pandemic. Specific issues such as transparency, accountability and effectiveness of assistance would be focussed. This study will be useful to provide guidelines to the management of philanthropy organisations towards sustainability and effective assistance in teaching and learning for B40 households.